1971
DOI: 10.1139/v71-298
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of the Electronically Excited Oxygen Atom O(1D2) with Nitrous Oxide

Abstract: An investigation has been made of the relative importance of the possible pathways [2a]–[2d][Formula: see text]for the reaction in the gas phase at room temperature between the excited oxygen atom O(1D2) and N2O, using the photolysis of NO2, O3, and N2O as sources of the excited atom. Measurement of the yields of N2 and NO from the photolysis at 2288 Å of mixtures of NO2 and N2O has led to a value of 1.01 ± 0.06 for k2a/k2b, the ratio of the rate constants for [2a] and [2b], in excellent agreement with the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1972
1972
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…In the absence of CaHe, the O(aP) disappears via No NO would be consumed, but 0 2 would be produced in addition to that from reaction (2). The O ( 3 P ) atom is known to react with C3Hs with a room-temperature rate constant of 4 The results of the studies with added C3H6 are shown in Table 11.…”
Section: B) Q 200mentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of CaHe, the O(aP) disappears via No NO would be consumed, but 0 2 would be produced in addition to that from reaction (2). The O ( 3 P ) atom is known to react with C3Hs with a room-temperature rate constant of 4 The results of the studies with added C3H6 are shown in Table 11.…”
Section: B) Q 200mentioning
confidence: 99%
“…The same ratio has also been measured carefully in Preston's laboratory [4] in three systems. From the photolysis of NO2 at 2288 A in the presence of N20, Each laboratory has produced O(l0) in three different ways, and each laboratory obtains internally consistent results.…”
Section: Introductionmentioning
confidence: 99%
“…For personal use only. On the other hand Preston and co-workers (8) found no evidence of a kinetic energy effect on the ratio k,,/k,,. More recently the ratio was redetermined in this laboratory by Wiebe and Paraskevopoulos (9); the value obtained agrees with that of Preston and co-workers and again it was found to be independent of the excess kinetic energy.…”
Section: Introductionmentioning
confidence: 91%
“…In the case of N,O it is thus possible to distinguish between the chemical reaction steps (2a and 2b) and the electronic deactivation step (2c), Although previous work (3,4) has indicated that reaction 2c is not important, the more direct test for 0 ( 3 P ) atoms by the neopentane technique (2) The N, generated in reactions 1 and 2a was measured In every experiment by gas-solid chromatography on a 18 ft 13X Molecular Sieve column. Neopentanol was separated from the unreacted reactants and measured on a 300 ft long, 0.015 in.…”
Section: Introductionmentioning
confidence: 99%